2020
DOI: 10.5213/inj.2040152.076
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy With Polydeoxyribonucleotide and Pirfenidone Alleviates Symptoms of Acute Respiratory Distress Syndrome in Human Lung Epithelial A549 Cells

Abstract: Purpose: Acute respiratory distress syndrome (ARDS) is characterized by its acute onset of symptoms such as bilateral pulmonary infiltrates, severe hypoxemia, and pulmonary edema. Many patients with ARDS survive in the acute phase, but then die from significant lung fibrosis.Methods: The effect of combination therapy with polydeoxyribonucleotide (PDRN) and pirfenidone on ARDS was investigated using human lung epithelial A549 cells. ARDS environment was induced by treatment with lipopolysaccharide and transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, co-administration of Ok-PDRN and pirfenidone was found to alleviate the effects of acute respiratory distress syndrome in human lung epithelial cells, which was induced using a combination of LPS (1 μg/mL) and tissue growth factor-β (TGF-β) (5 ng/mL) [ 24 ]. This study demonstrated that PDRN inhibited the expression of basic fibroblast growth factor (FGF), collagen (COL) I, connective TGF, and hydroxyproline.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, co-administration of Ok-PDRN and pirfenidone was found to alleviate the effects of acute respiratory distress syndrome in human lung epithelial cells, which was induced using a combination of LPS (1 μg/mL) and tissue growth factor-β (TGF-β) (5 ng/mL) [ 24 ]. This study demonstrated that PDRN inhibited the expression of basic fibroblast growth factor (FGF), collagen (COL) I, connective TGF, and hydroxyproline.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of collagen type I and fibroblast growth factor expressions. [ 43 ] Docosahexaenoic acids derived Resolvin D1 Mechanical stretch and acid-induced pulmonary fibrosis in mice and human lung epithelial (BEAS-2B) cells In vivo and in vitro Mice had the pulmonary fibrosis induced by intratracheal acid aspiration following mechanical ventilation for 24 h. Subsequently, mice were treated with resolvin D1 at 0.01, 0.1 and 1 μg for five consecutive days. Resolvin D1 at 0.01 nM/μL was used as pretreatment in BEAS-2B cells, which were exposed to acid for 10 min before being subjected to 48 h of mechanical stretch.…”
Section: Pharmaceutical Active Natural Products With Potential To Trementioning
confidence: 99%
“…Although less usual, the use of animal-derived PANPs could also be an interesting approach for the treatment of mild respiratory and asthma-like symptoms in unhospitalized COVID-19 patients. A noteworthy example is the use of nucleotides from DNA blends [ 43 ]. Polydeoxyribonucleotide and pirfedidone were assessed against LPS and TGF-β-induced ARDS in human lung epithelial cells (A549).…”
Section: Pharmaceutical Active Natural Products With Potential To Trementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the increase in inflammatory factors can be reduced by adenosine A2A receptor (A2AR) stimulation in lung injury [9,10]. One of the adenosine agonists, polydeoxyribonucleotide (PDRN) is known as a candidate for anti-inflammatory drugs by inhibiting inflammation and apoptosis by selectively stimulating A2AR in lung-injured animals.…”
Section: Introductionmentioning
confidence: 99%